Comparative analysis of ELISA & MALDI-TOF mass spectrometry methods for microcystins in freshwater samples - Grant, Jennifer Elizabeth; Turczyn, Andrew; Kadlec, Kimberly (My University, 2016)
This project was supported by a UW-Stout Research and Dissemination grant to present at the 2016 conference of the American Society of Biochemistry & Molecular Biology.
Color poster with text, images, and charts.
Keywords: Lake Menomin; ELISA; MALDI-TOF MS; Microcystins; Enzyme-linked immunosorbent assay; Matrix-assisted laser desorption-ionization; Mass spectrometry; Posters; Menomin, Lake (reservoir)